Peran Pola Asuh Orang Tua Terhadap Karakter Religius Anak Usia Dini 5 – 6 Tahun - fredericksen amseke (Montessori Jurnal Pendidikan Kristen Anak Usia Dini, 2024)
Parenting styles are very important for the growth and development of children, especially the child's religious character. Therefore, this study aims to examine parents' parenting patterns regarding the religious character of young children aged 5-6 years. This research uses quantitative methods. The data collection tool uses parents' parenting patterns and early childhood religious character. Participants in this research were 80 parents of students who attended school in Oebufu Village at Benyamin oebufu Kindergarten, Marantha oebufu Kindergarten and Agape Indah oebufu Kindergarten. The data analysis technique uses simple linear regression analysis. The results of this study prove that parental parenting has a positive and significant effect on the religious character of young children aged 5-6 years by 19.8%. The higher the parenting style of parents, the better the religious character of young children aged 5-6 years in Oebufu sub-district, Oebobo sub-district, Kupang city.